Monobutyrin can alleviate hepatic lipid dysmetabolism and improve liver mitochondrial ultrastructure and autophagy in high-fat diet mice - Yuqing Zhang; Xiaoteng Li; Haidong Wang; Kexin Zhang; Ji Qiu; Minyao Zhou; Minqi Wang (npj Science of Food)
Abstract The incidence of non-alcoholic fatty liver disease has proportionally escalated alongside the global epidemic of obesity. Monobutyrin (MB), a food additive found in butter and cod liver oil, possesses lipid-regulating properties. This study aimed to explore the alleviating effect of MB on liver oxidative injury and lipid metabolism in obese mice induced by a high-fat diet (HFD). The results showed that MB administration (1 or 2 g/kg body weight (BW)) for 8 weeks significantly reduced body weight, improved hepatic lipid metabolism via activation of the peroxisome proliferator-activated receptor α (PPARα) signaling pathway, and stabilized liver mitochondrial ultrastructure to alleviate oxidative liver injury by triggering mitochondrial autophagy through regulation of microtubule-associated protein 1A/1B-light chain 3 (LC3) and ubiquitin-binding protein (P62) in mice. Moreover, MB might increase the abundance of beneficial bacteria, promote short-chain fatty acid levels, and alleviate high-fat induced obesity via the gut-liver axis. These findings provide a novel insight into MB as an intervention strategy for hepatic metabolic disorders.